Wittgenstein as philosophical tone-poet : philosophy and music in dialogue - Szabados, Béla, 1942- (Studien zur österreichischen Philosophie, 2014)
This book provides the first in-depth exploration of the importance of music for Ludwig Wittgenstein's life and work. Wittgenstein's remarks on music are essential for understanding his philosophy: they are on the nature of musical understanding, the relation of music to language, the concepts of representation and expression, on melody, irony and aspect-perception, and, on the great composers belonging to the Austrian-German tradition. Biography and philosophy, this work suggests that Wittgenstein was a composer of philosophy who used the musical form as a blueprint for his own writing and th.